The pilot malaria vaccine program in Marindi Sub-County Hospital, Homa Bay, Kenya - Susan Atieno Onyango; VE ADAMU; G. O. Okomo; F. A. Oketch (Orapuh Journal, 2020)
Effective malaria control programs prevent transmission of malaria by promoting personal protective measures like the use of mosquito repellent creams, the use of mosquito net/coils, promoting effective vector control strategies like indoor residual spraying, and the provision of appropriate case management with early diagnosis and effective treatment. The Malaria vaccine is the proposed potential additional tool to complement the existing package of the WHO-recommended preventive, diagnostic, and treatment measures for malaria. Marindi Sub-County Hospital is one of the pilot sites where the Malaria Vaccine Program is being implemented in Kenya. Assessing the performance of the program is crucial in gauging the progress of the pilot program, identifying gaps/challenges, and formulating ways of addressing those challenges. We reviewed the records of children attending the Child Welfare Clinic (CWC) of the Marindi Sub-County Hospital and determined the number of children eligible for the malaria vaccine and those who got vaccinated between October 2019 and March 2020. 68.8%  of the eligible children was vaccinated during this period. The malaria vaccine program is yet to pick up well due to various challenges and is expected to take shape as the implementation continues if the proposed measures are put in place. To improve the situation, there is the need for more sensitization (using the local language and through some contextually relevant channels), on the job training for healthcare workers, the astute dissemination of relevant information to all and sundry and to make more vaccines available to the program and localities.